Method for the production of low-cost bio-based c / c composites and products thereof
Patent Information
- Application Number
- CN202611032821.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]为克服上述技术的不足,本发明的目的在于提出一种低成本生物基C/C复合材料的制备方法及其产品,解决现有技术中C/C复合材料成本较高、原材料受限、原料不可再生性和新型材料力学性能有待提升的问题
本发明提供的一种低成本生物基C/C复合材料的制备方法及其产品,采用木质素作为碳源之一,通过化学气相沉积和浸渍法获得产品,在可再生和降低成本的同时,保证了C/C复合材料的高拉伸强度、常温压缩性能和良好的抗烧蚀性能。
Smart Images

Figure CN122916705A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of C / C composite material molding technology, and in particular to a low-cost method for preparing bio-based C / C composite materials and its products. Background Technology
[0002] With the increasing demand for high-Mach speeds in spacecraft and growing cost awareness, the application of carbon / carbon (C / C) composites in solid rockets is constantly expanding. However, traditional C / C composites, due to their high cost, cannot completely replace high-temperature alloys in solid rockets; they only hold a favorable position due to their special functional requirements or lightweight requirements. The high cost of C / C composites is mainly limited by the price of raw materials. With the research and development and production of different tow carbon fibers, the price of carbon fiber has decreased from thousands of yuan / kg a decade ago to hundreds of yuan / kg today. However, the price of C / C composites is not only limited by the price of carbon fiber, but also by the raw materials of the carbon matrix. Currently, commonly used carbon matrices include deposited carbon, resin carbon, and pitch carbon, which are expensive and non-renewable.
[0003] C / C composite materials possess characteristics such as low density, good high-temperature mechanical properties, low coefficient of thermal expansion, and high thermal conductivity, making them suitable for applications in aerospace vehicles and solid rockets. However, traditional C / C composite materials suffer from inherent drawbacks such as high cost, limited raw material sources, dependence on petroleum, and non-renewability, which significantly restricts their widespread application and hinders their transition from the aerospace sector to the civilian market.
[0004] Therefore, providing a new, low-cost C / C composite material with good mechanical properties is of great significance to the aerospace field. Summary of the Invention
[0005] To overcome the shortcomings of the above-mentioned technologies, the purpose of this invention is to propose a low-cost method for preparing bio-based C / C composite materials and the products thereof, thereby solving the problems of high cost, limited raw materials, non-renewable raw materials, and the need to improve the mechanical properties of new materials in the existing C / C composite materials.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a low-cost bio-based C / C composite material is characterized by including graphitizing a carbon fiber braid to obtain a graphitized braid; subsequently, performing vapor deposition on the graphitized braid in a mixed gas environment of natural gas and nitrogen to obtain a C / C preform; and finally, using the C / C preform and slurry as raw materials, obtaining the C / C composite material by an impregnation method; wherein the slurry is made from lignin, graphite powder, and benzyl alcohol.
[0007] As a preferred embodiment, the carbon fiber braid is a braided body with a certain geometric shape, structure, and fiber orientation, made from carbon fibers through a textile process. Textile processes include weaving, knitting, sewing, and piercing; carbon fibers include carbon fiber cloth and carbon fiber bundles. This invention does not limit the shape of the braided body; those skilled in the art can choose according to the actual situation.
[0008] As a preferred embodiment, the density of the carbon fiber braid is 0.75-0.85 g / cm³. 3 .
[0009] As a preferred embodiment, the graphitization process includes heating the carbon fiber braid to 1800-2000℃ under a protective atmosphere and holding it at that temperature for 150-250 minutes to obtain a graphitized braid.
[0010] Specifically, the graphitization process is carried out in a graphitization furnace; the graphitization process includes: after evacuating the furnace, introducing a protective atmosphere and maintaining the furnace pressure at 2-5 kPa, heating the carbon fiber braid to 1800-2000℃ at a heating rate of 4-6℃ / min, and holding at this temperature for 150-250min for graphitization treatment; after the holding period, cooling the material to 90-110℃ with the furnace, opening the furnace, and removing the material to obtain the graphitized braid. The highest graphitization temperature of 1800-2000℃ in this invention is 300-400℃ lower than the graphitization temperature of 2100-2400℃ in conventional methods, and it has good compatibility with the carbon fiber braid fabric process used in this invention.
[0011] As a preferred embodiment, the vapor deposition process includes heating the graphitized braid under a protective atmosphere. When the temperature reaches 1000°C, the protective atmosphere is stopped, and a mixture of natural gas and nitrogen is introduced instead. The furnace pressure is maintained at 3-4 kPa, and heating continues until the temperature reaches 1200-1300°C and is held for 6-8 hours to obtain a C / C billet.
[0012] Specifically, the vapor deposition process is carried out in a vapor deposition furnace; the vapor deposition process includes: evacuating the vapor deposition furnace, introducing a protective atmosphere and maintaining a furnace pressure of 2-5 kPa, heating the graphitized braided material, and when the temperature reaches 1000℃, stopping the introduction of the protective atmosphere and replacing it with a mixed gas of natural gas and nitrogen at a flow rate of 3-4 L / min, maintaining a furnace pressure of 3-4 kPa, continuing heating to 1200-1300℃ and holding for 6-8 hours, at which point C / C billet begins to form. After the holding period, heating is stopped, maintaining the furnace pressure, cooling with the furnace to 100℃, and then removing from the furnace to obtain the C / C billet.
[0013] Furthermore, the heating process of the graphitized braid includes: first, heating the graphitized braid to 450-550℃ at a heating rate of 2-3℃ / min, then heating to 650-750℃ at a heating rate of 0.25-0.75℃ / min, followed by heating to 850-950℃ at a heating rate of 1-3℃ / min, then heating to 1050-1150℃ at a heating rate of 2-3℃ / min, and finally heating to 1200-1300℃ at a heating rate of 3-5℃ / min, and holding at that temperature for 6-8 hours. Gradient heating ensures the removal of residual impurities, water molecules, oxygen, etc., in the furnace. Additionally, it allows for the control of the gas-phase reaction, enabling the coated carbon to grow slowly on the carbon fiber surface, avoiding the peeling of deposited carbon due to thermal expansion stress.
[0014] Furthermore, during the graphitization and vapor deposition processes, the flow rate of the protective atmosphere is 4-5 L / min; the protective atmosphere used in the graphitization process is argon; and the protective atmosphere used in the vapor deposition process is nitrogen. The protective atmosphere is maintained only during the initial heating phase to 1000℃ in the vapor deposition process, while the protective atmosphere is used throughout the entire graphitization process.
[0015] As a preferred embodiment, the volume ratio of natural gas to nitrogen in the natural gas and nitrogen mixture is (0.55-0.75):1. Natural gas is used as the carbon source gas. If the volume ratio of natural gas to nitrogen is too low, it will lead to reduced product weight gain efficiency, thereby lengthening the material production cycle and reducing raw material utilization. If the volume ratio of natural gas to nitrogen is too high, it will cause excessive concentration of pyrolysis carbon, clogging the ventilation channels and causing excessive impurities, resulting in a decline in product quality and adversely affecting the overall material performance.
[0016] As a preferred embodiment, the impregnation method includes immersing the C / C preform in a slurry, performing impregnation treatment under a protective atmosphere and positive pressure, and then performing high-temperature treatment under a protective atmosphere to obtain the C / C composite material. The slurry is a mixed slurry prepared by wet ball milling of lignin, graphite powder, and benzyl alcohol, and stored in a vacuum tank for later use. The mass ratio of lignin, graphite powder, and benzyl alcohol in the slurry is 1:0.2-0.4:1; the mass ratio of the C / C preform to the slurry is 1:2-4. If the proportion of graphite powder in the slurry is too low, the product will have poor densification, poor surface quality, and an uneven surface. If the proportion of graphite powder in the slurry is too high, the slurry will not be evenly dispersed, easily forming a crust on the surface of the C / C preform, resulting in a large number of closed cells and affecting the material properties.
[0017] As a preferred embodiment, the weight-average molecular weight of the lignin is in the range of 5000-8000 Da.
[0018] Further, during the impregnation process, the impregnation pressure is 3-4 MPa, and the holding time is 30-60 min; after impregnation, the pressure is released and a high-temperature treatment is performed; the high-temperature treatment includes: heating the C / C preform impregnated with the slurry to 2100-2300℃ at a heating rate of 2-4℃ / min, and holding at that temperature for 150-250 min; wherein the flow rate of the protective atmosphere is 1.2-1.4 L / min. In this process, the slurry first completes curing, and then the cured matrix carbon composite decomposes to form carbon, which is then impregnated into the porous structure of the C / C preform through capillary force to react and obtain the C / C composite material.
[0019] This invention does not limit the type of protective atmosphere, and those skilled in the art can select it according to the actual situation. For example, the protective atmosphere can be nitrogen or argon, etc.
[0020] The present invention also provides a low-cost bio-based C / C composite material, which is prepared by the above preparation method.
[0021] As a preferred embodiment, the low-cost bio-based C / C composite material exhibits a tensile strength ≥179MPa under a temperature holding time of -70℃ for 4 hours, a tensile strength ≥180MPa at 25℃, a compressive strength ≥350MPa at 25℃, and a plasma ablation rate ≤0.02mm / s under 1Ma alumina particle erosion.
[0022] Compared with the prior art, the beneficial effects of the present invention include: This invention provides a low-cost method for preparing bio-based C / C composite materials and the product thereof. The method uses lignin as one of the carbon sources and obtains the product through chemical vapor deposition and impregnation. While being renewable and reducing costs, it ensures the high tensile strength, room temperature compression performance and good ablation resistance of the C / C composite material.
[0023] The C / C composite material of this invention exhibits excellent plasma ablation rate (1 Ma alumina particle erosion), comparable to that of C / C composite materials prepared from chemical raw materials. It also possesses good mechanical properties, preventing deformation due to overheating and avoiding thermal stress that could damage other assembled parts. Compared to C / C composite materials prepared from general-purpose raw materials, the C / C composite material of this invention has lower cost, a wider range of raw material sources, and uses renewable raw materials. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the structure of a typical component for an aircraft prepared in Example 1; Figure 2 This is a schematic diagram of the graphite-shaped vent pipe in Example 1. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0026] Example 1 A low-cost bio-based C / C composite material includes a fiber skeleton, deposited carbon, and matrix carbon; wherein the fiber skeleton is a graphitized carbon fiber braid, which serves as the supporting skeleton of the C / C composite material; the surface of the fiber skeleton is loaded with deposited carbon through vapor deposition; finally, the interior of the fiber skeleton is filled with matrix carbon through high-pressure impregnation and high-temperature curing; the carbon source of the matrix carbon is lignin.
[0027] The preparation method of the above-mentioned low-cost bio-based C / C composite material includes the following steps: 1) Graphitize the carbon fiber braid to obtain a graphitized braid; 1.1) Preparation of carbon fiber braided fabric The carbon fiber braided structure employs a stitched construction. The braided structure requires alternating layers of T800 carbon fiber cloth and carbon felt, plus an additional ±45° carbon fiber mesh layer wound and laid up. The thickness direction is achieved using bidirectional puncture stitching with a single strand of T1000 carbon fiber, with a stitch spacing of 3×3 mm. The density of the carbon fiber braided structure is 0.80 g / cm³. 3 .
[0028] 1.2) Fix the carbon fiber braid onto the graphite tooling mold of the fitting surface, place the graphite tooling mold into the graphitization furnace, close the furnace door, and evacuate to below 200 Pa. The process of evacuating to below 200 Pa is as follows: first evacuate to below 200 Pa; then introduce argon gas as a protective atmosphere until the furnace pressure is above 100 kPa; repeat the evacuation and argon gas introduction process 3 times to remove air from the furnace, and finally evacuate to below 200 Pa.
[0029] 1.3) Introduce argon gas again until the pressure inside the furnace is above 100 kPa, close the gas filling valve, and evacuate the furnace again to below 200 Pa. Repeat this process 3 times, and finally keep the furnace evacuated to below 200 Pa. 1.4) Next, argon gas is introduced to maintain the pressure inside the furnace at 3.5 kPa. The carbon fiber braid is then heated at a rate of 5 °C / min. The temperature is raised to 1900 °C and held for 200 min for graphitization treatment. 1.5) After the heat preservation is completed, the furnace is cooled to 100°C, the furnace is opened and the material is removed to obtain the graphitized braided body, which is the fiber skeleton of the C / C composite material. The argon gas flow rate is 4.5 L / min.
[0030] 2) Deposition: The graphitized braided fabric is placed in a vapor deposition furnace and heated under a protective atmosphere. When the temperature reaches 1000℃, the protective atmosphere is stopped, and a mixture of natural gas and nitrogen is introduced while maintaining the furnace pressure at 3.5 kPa. Heating continues until the temperature reaches 1250℃ and is held for 7 hours to obtain the C / C billet. Nitrogen is used as the protective atmosphere, and the natural gas and nitrogen are ordinary domestic natural gas and industrial nitrogen, respectively. The C / C billet is a fiber skeleton loaded with deposited carbon.
[0031] 2.1) Fix the graphitized braided body onto the graphite tooling distribution plate of the fitted profile, and attach the graphite contoured vent pipe. Place the graphite tooling distribution plate and the graphitized braided body into the vapor deposition furnace, close the furnace door, and evacuate to below 200 Pa. The process of evacuating to below 200 Pa is as follows: first, evacuate to below 200 Pa; then, introduce a protective atmosphere of nitrogen until the pressure reaches above 100 kPa; repeat the evacuation and nitrogen introduction process three times to remove air from the furnace, and finally evacuate to below 200 Pa.
[0032] 2.2) Nitrogen gas was introduced at a flow rate of 4.5 L / min, and the furnace pressure was maintained at 3.5 kPa. Then, heating was started. The heating process was as follows: the graphitized braid was heated to 500℃ at a heating rate of 2.5℃ / min, to 700℃ at a heating rate of 0.5℃ / min, to 900℃ at a heating rate of 2℃ / min, to 1100℃ at a heating rate of 2.5℃ / min, and to 1250℃ at a heating rate of 4℃ / min, and held at that temperature for 7 hours. When the temperature reached 1000℃, the nitrogen gas was stopped, and a mixture of natural gas and nitrogen in a volume ratio of 0.6:1 was introduced at a flow rate of 3.5 L / min, while maintaining the furnace pressure at 3.5 kPa.
[0033] 2.3) After the heat preservation is completed, maintain the pressure inside the furnace and cool it to 100°C with the furnace. Open the furnace and take out the material to obtain C / C billet.
[0034] 3) Finally, using C / C preforms and slurry as raw materials, C / C composite materials are obtained through an impregnation method; the slurry is made from lignin, graphite powder, and benzyl alcohol. The impregnation method includes immersing the C / C preforms in the slurry, performing impregnation treatment sequentially under a protective atmosphere and positive pressure, and then performing high-temperature treatment under a protective atmosphere to obtain the C / C composite material.
[0035] 3.1) Preparation of slurry Lignin, graphite powder, and benzyl alcohol were mixed in a mass ratio of 1:0.3:1, then wet-milled into a homogeneous slurry. The slurry was then placed in a vacuum chamber and vacuumed to 100 Pa for storage and use. The weight-average molecular weight of the lignin ranged from 5000 to 8000 Da.
[0036] 3.2) Positive pressure impregnation composite molding The C / C billet was placed in a graphite tooling mold containing a slurry for fitting a specific impregnation surface, ensuring the C / C billet was completely submerged in the slurry. The mass ratio of C / C billet to slurry was 1:3. The graphite tooling mold was then placed in a graphitization furnace, and argon gas was introduced as a protective atmosphere and maintained at a positive pressure of 3.5 MPa for 45 min. After depressurization, high-temperature treatment was performed. The high-temperature treatment included heating the C / C billet impregnated with the slurry to 2200℃ at a heating rate of 3℃ / min under argon gas conditions, holding at that temperature for 200 min, and then cooling to room temperature with the furnace. The slurry preferentially solidified, and the solidified matrix decomposed into carbon, which remained in the porous body and reacted to obtain the C / C composite material, thus completing the material preparation. The argon gas introduction rate was 1.3 L / min.
[0037] By repeating step 3) for a total of four cycles of matrix densification, a product that meets the requirements can be obtained.
[0038] In this embodiment, the product is a typical component of an aircraft, and its manufacturing process utilizes a carbon fiber braided structure as shown in the example below. Figure 1 As shown, the component is trumpet-shaped, with one end (larger in diameter) being open and the other end being closed. For example... Figure 2 As shown, the graphite-shaped ventilation tube is a trumpet-shaped structure with openings at both ends, consistent with the structure and shape of the carbon fiber braid. It is trumpet-shaped with openings at both ends, and each part is larger than the carbon fiber braid, with an inner diameter up to 200mm larger. This allows the graphite-shaped ventilation tube to be fitted onto the outside of the carbon fiber braid, and mixed gas is delivered into the graphite-shaped ventilation tube through one end opening. This ensures that the mixed gas fully contacts the carbon fiber braid, improving deposition quality and increasing the utilization rate of carbon source gas.
[0039] After implementing the above methods, the performance of the five groups of samples from the same batch was tested, and the results are shown in Table 1. Density was measured using the volumetric method; tensile strength at -70℃ and 25℃ was obtained according to GB / T 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics"; compressive strength at 25℃ was obtained according to JB / T 8133.8-2013 "Test Methods for Physicochemical Properties of Electro-Carbonized Products Part 8: Compressive Strength"; and plasma ablation rate under 1 Mach alumina particle erosion conditions was obtained according to GJB 323B-2018 "Test Method for Ablation of Ablation Materials".
[0040] Table 1: Performance test results of C / C composite material in Example 1 As shown in Table 1, the bio-based C / C composite material prepared by the method of this invention has low density and high compressive strength. The tensile strength at -70℃ for 4 hours is 181-192 MPa, the tensile strength at 25℃ is 186-193 MPa, and the compressive strength at 25℃ is 368-381 MPa. The plasma ablation rate under 1 Ma alumina particle erosion is 0.005-0.011 mm / s, indicating that the bio-based C / C composite material of this invention has excellent tensile properties at both -70℃ and 25℃, with minimal fluctuation in material properties and good ablation resistance. Under low-temperature conditions, the tensile behavior of the material is mainly due to the high utilization rate of fiber strength, suitable bonding force between the carbon matrix and the carbon fiber surface, and the absence of brittle fracture in the fibers. Even after cracks appear in the tensile samples, a certain degree of yielding behavior is observed.
[0041] The five groups of samples prepared in the same batch were stored in a -70℃ insulated container for 4 days, then taken out and cooled to room temperature. This was repeated 100 times as one cycle. Then, tensile strength, compressive strength and plasma ablation performance were tested. The results are shown in Table 2.
[0042] Table 2: Performance results of C / C composite material in Example 1 after 100 cycles of low temperature / room temperature cycling As can be seen from Table 2, the performance of the bio-based low-cost C / C composite material prepared by this invention is not sensitive to the effects of long-term low-temperature cycling, and the material properties are basically stable. The tensile strength is maintained above 180 MPa on average, and the plasma ablation performance is maintained at around 0.01 mm / s.
[0043] Example 2 The difference between this embodiment and Embodiment 1 is that: In step 1), the density of the carbon fiber braid is 0.75 g / cm³. 3 The argon gas flow rate is 4 L / min; when argon gas is introduced for graphitization, the furnace pressure is maintained at 2 kPa; during graphitization, the heating rate is 4℃ / min, the graphitization temperature is 1800℃, and the holding time is 150 min; after the holding time is completed, the furnace is cooled to 90℃.
[0044] In step 2.2), nitrogen gas is introduced at a flow rate of 4 L / min, maintaining the furnace pressure at 2 kPa. Then, the temperature is raised in the following steps: the temperature is raised to 450℃ at a rate of 2℃ / min, to 650℃ at a rate of 0.25℃ / min, to 850℃ at a rate of 1℃ / min, to 1050℃ at a rate of 2℃ / min, and to 1200℃ at a rate of 3℃ / min, and held at this temperature for 6 hours. When the temperature reaches 1000℃, the nitrogen gas is stopped, and a mixture of natural gas and nitrogen in a volume ratio of 0.55:1 is introduced at a flow rate of 3 L / min, maintaining the furnace pressure at 3 kPa.
[0045] In step 3), the mass ratio of lignin, graphite powder, and benzyl alcohol is 1:0.2:1; the mass ratio of C / C billet to slurry is 1:2; the positive pressure is 3 MPa, and the holding time is 30 min; in the high-temperature treatment process, the heating rate is 2℃ / min, the high-temperature treatment temperature is 2100℃, and the holding time is 150 min; the argon gas introduction rate is 1.2 L / min.
[0046] After implementing the above method, the five groups of samples from the same batch were subjected to performance testing, and the results are shown in Table 3.
[0047] Table 3: Performance test results of C / C composite material in Example 2 As shown in Table 3, the bio-based C / C composite material prepared by the method of the present invention has low density and high compressive strength. The tensile strength at -70℃ for 4 hours is 179-189 MPa, the tensile strength at 25℃ is 184-191 MPa, the compressive strength at 25℃ is 350-386 MPa, and the plasma ablation rate under 1 Ma alumina particle erosion is 0.008-0.012 mm / s. This indicates that the bio-based C / C composite material of the present invention has good mechanical properties at both -70℃ and 25℃, and the material properties produced have small fluctuations and good ablation resistance.
[0048] Example 3 The difference between this embodiment and Embodiment 1 is that: In step 1), the density of the carbon fiber braid is 0.85 g / cm³. 3 The argon gas flow rate is 5 L / min; when argon gas is introduced for graphitization, the furnace pressure is maintained at 5 kPa; during graphitization, the heating rate is 6℃ / min, the graphitization temperature is 2000℃, and the holding time is 250 min; after the holding time is completed, the furnace is cooled to 110℃.
[0049] In step 2.2), nitrogen gas is introduced at a flow rate of 5 L / min to maintain the furnace pressure at 5 kPa. Then, the temperature is raised in the following steps: the temperature is raised to 550℃ at a rate of 3℃ / min, to 750℃ at a rate of 0.75℃ / min, to 950℃ at a rate of 3℃ / min, to 1150℃ at a rate of 3℃ / min, and to 1300℃ at a rate of 5℃ / min, and held at this temperature for 8 hours. When the temperature reaches 1000℃, the nitrogen gas is stopped, and a mixture of natural gas and nitrogen in a volume ratio of 0.75:1 is introduced at a flow rate of 4 L / min, maintaining the furnace pressure at 4 kPa.
[0050] In step 3), the mass ratio of lignin, graphite powder, and benzyl alcohol is 1:0.4:1; the mass ratio of C / C billet to slurry is 1:4; the positive pressure is 4 MPa, and the holding time is 60 min; in the high-temperature treatment process, the heating rate is 4℃ / min, the high-temperature treatment temperature is 2300℃, and the holding time is 250 min; the argon gas introduction rate is 1.4 L / min.
[0051] After implementing the above method, the five groups of samples from the same batch were subjected to performance testing, and the results are shown in Table 4.
[0052] Table 4: Performance test results of C / C composite material in Example 3 As shown in Table 4, the bio-based C / C composite material prepared by the method of the present invention has low density and high compressive strength. The tensile strength at -70℃ for 4 hours is 183-192 MPa, the tensile strength at 25℃ is 181-195 MPa, the compressive strength at 25℃ is 371-388 MPa, and the plasma ablation rate under 1 Ma alumina particle erosion is 0.005-0.010 mm / s. This indicates that the bio-based C / C composite material of the present invention has good tensile properties at both -70℃ and 25℃, and the material properties produced have small fluctuations and good ablation resistance.
[0053] The cost and preparation cycle of the bio-based C / C composite material in Example 1 of this invention were calculated compared with those of traditional resin-based and asphalt-based C / C composite materials. The results are shown in Table 5. Table 5 shows that the raw material cost and production cycle of the present invention are lower than those of the traditional methods.
[0054] Table 5: Cost / Cycle Comparison of the Carbon-Carbon Composite Material of the Invention with Traditional Carbon-Carbon Composite Materials In summary, this invention solves the problem of high costs in the preparation of C / C composite materials by using lignin, a widely available and inexpensive raw material, to replace resin and mesophase pitch as one of the carbon sources, thus providing feasibility for large-scale industrial production. Furthermore, lignin, a natural macromolecular polymer, can form hydrogen bonds between phenolic hydroxyl hydrogen atoms and alkyl hydroxyl oxygen atoms in its structural units, and π-π conjugation occurs between benzene rings. During liquid-phase ball milling, it spontaneously forms micron-sized spherical gels that autonomously encapsulate graphite powder. Through these physical and chemical interactions, the problem of solid-phase dispersion of the carbon source slurry is solved, improving the densification uniformity of the C / C composite material. In addition, lignin not only acts as a carbon source during slurry impregnation but also paves the way for efficient densification by filling graphite powder into the C / C preform. The slurry impregnation requires additional pressure; pressurized impregnation allows the solid carbon source in the slurry to better wet the pores of the braid, reducing low-density areas in the C / C composite material and improving the densification uniformity. This invention shortens the preparation time and improves production efficiency by using a deposition method and a slurry pressure impregnation molding technology.
[0055] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a low-cost bio-based C / C composite material, characterized in that, The process includes graphitizing a carbon fiber braid to obtain a graphitized braid; then performing vapor deposition on the graphitized braid in a mixed gas environment of natural gas and nitrogen to obtain a C / C preform; finally, using the C / C preform and slurry as raw materials, obtaining a C / C composite material by impregnation; wherein the slurry is made from lignin, graphite powder, and benzyl alcohol.
2. The preparation method according to claim 1, characterized in that, The carbon fiber braided body is a braided body with a certain geometric shape, structure and fiber orientation made of carbon fiber through a textile process.
3. The preparation method according to claim 2, characterized in that, The density of the carbon fiber braid is 0.75-0.85 g / cm³. 3 .
4. The preparation method according to claim 1, characterized in that, The graphitization process includes heating the carbon fiber braid to 1800-2000℃ under a protective atmosphere and holding it at that temperature for 150-250 minutes.
5. The preparation method according to claim 1, characterized in that, The vapor deposition process includes heating the graphitized braid under a protective atmosphere. When the temperature reaches 1000°C, the protective atmosphere is stopped, and a mixture of natural gas and nitrogen is introduced instead. The furnace pressure is maintained at 3-4 kPa and heating continues until the temperature reaches 1200-1300°C and is held for 6-8 hours to obtain C / C billet.
6. The preparation method according to claim 5, characterized in that, The heating process of the graphitized braid includes: first, heating the graphitized braid to 450-550℃ at a heating rate of 2-3℃ / min, then heating to 650-750℃ at a heating rate of 0.25-0.75℃ / min, then heating to 850-950℃ at a heating rate of 1-3℃ / min, then heating to 1050-1150℃ at a heating rate of 2-3℃ / min, and finally heating to 1200-1300℃ at a heating rate of 3-5℃ / min, and holding at that temperature for 6-8 hours.
7. The preparation method according to claim 1, characterized in that, In the mixture of natural gas and nitrogen, the volume ratio of natural gas to nitrogen is (0.55-0.75):
1.
8. The preparation method according to any one of claims 1-7, characterized in that, The impregnation method includes immersing the C / C preform in a slurry, performing impregnation treatment under a protective atmosphere and a positive pressure of 3-4 MPa, and then performing high-temperature treatment under a protective atmosphere to obtain the C / C composite material; wherein, the slurry is a mixed slurry prepared by wet ball milling of lignin, graphite powder, and benzyl alcohol; the mass ratio of lignin, graphite powder, and benzyl alcohol in the slurry is 1:0.2-0.4:1; and the mass ratio of the C / C preform to the slurry is 1:2-4.
9. The preparation method according to claim 8, characterized in that, The high-temperature treatment includes: heating the C / C billet impregnated with slurry to 2100-2300℃ at a heating rate of 2-4℃ / min, and holding it at that temperature for 150-250min.
10. A low-cost bio-based C / C composite material, characterized in that, The C / C composite material is prepared by any one of the preparation methods described in claims 1-9; the tensile strength of the C / C composite material is ≥179MPa under the condition of holding at -70℃ for 4h, the tensile strength is ≥180MPa at 25℃, the compressive strength is ≥350MPa at 25℃, and the plasma ablation rate under 1Ma alumina particle erosion is ≤0.02mm / s.